Counter-terrorism laws and freedom of expression : global perspectives - Workneh, Téwodros Herausgeber; Haridakis, Paul, 1957- 1957- Herausgeber (Lexington Books, 2021)
Counter-terrorism laws in the International frame : uncertain times for freedom of expression / Téwodros Workneh and Paul Haridakis -- Schizorevolutions versus microfascisms : the fear of anarchy in state securitization / Athina Karatzogianni and Andrew Robinson -- Parliamentary discussion of counter-terrorism in Portugal : discourses on the right and on the left / Eunice Castro Seixas -- Anti-terrorism regulations and freedom of speech in Spain / Isabel Serrano Maillo -- Counter-terrorism gone digital : framing cybercrime in Turkey / Nazli Bülay Doğan -- Chinese-speaking netizens' comments on VOA's coverage of China's counter-terrorism laws and Freedom of Speech / Wei Sun -- Terrorism and counter-terrorism legislation in Brazil / Daniel Oppermann -- How 9/11 changed America and how we (can) talk about it : torture and the Guantanamo Military Commissions / Rita Radostitz --^